بناء نموذج للتنبؤ بالهطل المطري السنوي في محطة حصن سليمان باستخدام النمذجة الرياضية - عمار غطفان; حايك شريف; حمدان نزار (Latakia University Journal -Engineering Sciences Series, 2017)
نظراً لأهمية المياه وازدياد الحاجة إليها في الوقت الحاضر نتيجةً للتطور الكبير الحاصل في جميع مجالات الحياة الاقتصادية والاجتماعية, وباعتبار التقييم والتخطيط وإدارة المصادر المائية أحد المواضيع الهامة في الحياة البشرية وبالأخص في المناطق التي تتميز بندرة الهطولات المطرية أو التي يكون فيها التوزيع المطري رديئاً أو غير منتظم بحيث لا يمكن استخدامه للأغراض المختلفة. من هنا أتت أهمية البحث في التنبؤ بالهطل المطري في محطة حصن سليمان, ولتحقيق هذا الهدف فقد استُخدمت بيانات السلسلة الزمنية لمعدل الهطل المطري السنوي في محطة حصن سليمان الواقعة في محافظة طرطوس على خط الطول 36°15’ و خط العرض34°56’ للفترة بين عامي1959-2011, وقد استُخدمت في الدراسة منهجية بوكس – جنكنز التي تعتمد على إيجاد التنبؤات المستقبلية لسلسلة البيانات الأصلية. كما تم استخدام البرامج Minitab و Excel في الجانب الإحصائي وإعداد نتائج الدراسة. توصلت الدراسة إلى أن الهطل المطري في محطة حصن سليمان متناقص وقد بلغ هذا التناقص 3,7 ملم في العام خلال فترة الرصد, كما توصلت إلى بناء نموذج (ARIMA) المناسب للسلسلة بعد أن اجتاز مختلف الاختبارات الإحصائية المطلوبة، وكان النموذج ARIMA(1,0,0) هو النموذج المناسب لتمثيل البيانات والنموذج ARIMA(4,1,5) هو النموذج المناسب للتنبؤ بالهطل المطري المستقبلي. Due to the importance of water, and the increasing of demand at the present time due to the tremendous development in all spheres of economic and social life, and as the evaluation, planning and management of water sources, one of the important topics in human life, especially in areas with scarce rainfall or where rainfall distribution is poor or irregular so cannot be used for different purposes. From here, the importance of the research in forecasting rainfall in the Husn Suleiman station, comes, and to achieve this goal the data of time series for the average annual rainfall precipitation been used in Husn Suleiman station which located in the province of Tartous on longitude 36 ° 15 ’ andlatitude 34 ° 56’, for the period between 1959-2011, The methodology of "Box – Jenkins" been used in the study, this methodology relies on finding future forecasts from original data series. Also,the applications “MINITAB, EXCEL” have been used in the statistical side and the preparation of the study results. As a result, the study found that rainfall value in the ’Husn Suleiman station’ decreasing, this decline amounted to 3.7 mm per year during the monitoring period. Also, the appropriate (ARIMA) model for the series was build after it passed the various statistical tests are required, and founded that ARIMA(1,0,0) model is a good representation of the data and the ARIMA(4,1,5) model is the right model to forecast future rainfall.